Analysis of Midwife Needs Based On Workload In The Obgyn And Child Poly Work Unit At RSKIA HARYANDA Using the Workload Indicator of Staffing Need (WISN) Method - Sarah Agustina; Nuraini (CV. Inara, 2026)
Hospitals are required to provide quality health services through the availability of adequate human resources, including midwives. The mismatch between the number of personnel and the workload can affect the effectiveness of services and the quality of midwifery care. This study aims to analyze the needs of midwives based on workload using the Workload Indicators of Staffing Need (WISN) method. The research uses a quantitative descriptive approach. Data was obtained from secondary data in the form of the number of midwife service activities for one year and primary data through observation of the use of working time in each main activity. The analysis was carried out by calculating available working hours, workload standards, allowance standards, and manpower requirements based on WISN guidelines, then comparing them with the number of available midwives. The results of the analysis are expected to be able to describe the level of adequacy of midwives, identify shortages or over-staff, and become the basis for planning human resource needs in hospitals. The application of the WISN method provides a more objective calculation of manpower needs and is based on actual workload so that it can support management decision-making in the arrangement of health workers, improve the efficiency of human resource utilization, and optimize the quality of midwifery services in hospitals.